2021
DOI: 10.1038/s41419-021-03641-8
|View full text |Cite
|
Sign up to set email alerts
|

LDHA induces EMT gene transcription and regulates autophagy to promote the metastasis and tumorigenesis of papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is one of the most common kinds of endocrine-related cancer and has a heterogeneous prognosis. Metabolic reprogramming is one of the hallmarks of cancers. Aberrant glucose metabolism is associated with malignant biological behavior. However, the functions and mechanisms of glucose metabolism genes in PTC are not fully understood. Thus, data from The Cancer Genome Atlas database were analyzed, and lactate dehydrogenase A (LDHA) was determined to be a potential novel diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…The gap between LDHA and EMT was bridged by a study showing that high levels of LDHA lead to increased levels of acetyl-CoA, which increased the histone acetylation of EMT-related genes, including CTNNB1 , RHOB , and TGFβR1 , thus, promoting EMT ( Figure 4 ) [ 192 ]. LDHA ↑ ⇒ acetyl-CoA ↑ ⇒ CTNNB1, RHOB, TGFβ R1 ↑ ⇒ EMT …”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%
“…The gap between LDHA and EMT was bridged by a study showing that high levels of LDHA lead to increased levels of acetyl-CoA, which increased the histone acetylation of EMT-related genes, including CTNNB1 , RHOB , and TGFβR1 , thus, promoting EMT ( Figure 4 ) [ 192 ]. LDHA ↑ ⇒ acetyl-CoA ↑ ⇒ CTNNB1, RHOB, TGFβ R1 ↑ ⇒ EMT …”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%
“…In fact, knockdown experiments in PTC cell lines revealed that LDHA promotes the transcription of EMT-related genes, including catenin beta 1 (CTNNB1), ras homologue family member B (RHOB) and TGF receptor 1 (TGFR1), to promote migration and invasion. The mechanism involves the release of intracellular acetyl-CoA, which enhances the histone acetylation of these EMT-related genes [46]. Consistent with these results, another study showed that LDHA and glycolysis were critical for PTC progression [70].…”
Section: Thyroid Cancer Progression and Reciprocal Role Of Epithelial-mesenchymal Transition And Metabolic Rewiringmentioning
confidence: 65%
“…LDHA expression levels, in particular, positively correlate with the tall cell variant, which has a more aggressive clinical behavior compared with the classical PTCs and the more advanced tumor-node-metastasis (TNM) stage. Consistently, in 185 PTCs analyzed by immunohistochemistry, high expression levels of LDHA were associated with aggressive clinicopathological features and poor prognosis, and LDHA expression level resulted an independent prognostic marker for PTCs as it is the TNM stage [46].…”
Section: Glucose Metabolismmentioning
confidence: 69%
“…reported that LDHA not only promoted PTC tumorigenesis but also migration and invasion by regulating autophagy and inducing EMT gene transcription. Moreover, they also found that the metabolic products catalyzed by LDHA increased the acetylation of the related H3K27 and induced EMT ( 32 ). LDHA is phosphorylated by HER2 and SRC39, resulting in the increased invasive and metastatic potential of head and neck cancer ( 33 ).…”
Section: Metabolic Changes In Tumor Cellsmentioning
confidence: 98%
“…In conclusion, the expression of metabolism-related molecules revealed the differences in invasiveness and prognosis between different TC subtypes ( Figure 4 ). Numerous studies have demonstrated the relationship between the prognosis of thyroid carcinoma and glycolysis-related proteins such as GLUT, LDHA, MCT1 ( 32 , 135 , 136 ). Some studies have indicated that GLUT contributed to the increased glucose uptake observed during carcinogenesis ( 135 , 137 ).…”
Section: Prognostic Biomarkers and Treatmentmentioning
confidence: 99%